Functioning of the hypothalamic–pituitary–adrenal and growth hormone axes in frequently unexplained disorders: Results of a population study. (23rd October 2013) - Aggarwal, V.R.; Macfarlane, G.J.; Tajar, A.; Mulvey, M.R.; Power, A.; Ray, D.; McBeth, J.
Abstract Background The aim of the study was to test the hypothesis that associations with specific stress systems [hypothalamic–pituitary–adrenal (HPA) and growth hormone (GH) axes] would increase as the number of unexplained disorders increased while accounting for the possible confounding effects of psychosocial factors. Methods A cross‐sectional study identified those reporting chronic widespread pain, irritable bowel syndrome, chronic orofacial pain and chronic fatigue. Of the 1315 subjects, disorder status was available for 1180 (89.7%), of whom 766 (64.9%) reported no disorders, 277 (23.5%) reported one and 137 (11.6%) reported two or more. Eighty subjects were sought from each group for assessment of HPA (morning 8:00 a.m. and evening 10:00 p.m. saliva, and post‐dexamethasone serum cortisol levels) and GH [serum insulin‐like growth factor 1 (IGF‐1) level] axis function. Validated questionnaires informed current psychological state. Results Two hundred twenty‐seven subjects participated [79 (35%) with no disorders, 78 (34%) with one disorder and 70 (31%) with two or more disorders]. There were no significant associations (p < 0.05) between individual disorders or an increasing disorder load with any of the neuroendocrine levels measured: saliva/serum cortisol, IGF‐1 and dehydroepiandrosterone. Psychosocial factors were independently associated with disorders and with an increasing disorder load: health anxiety p < 0.01, anxiety p < 0.01, depression p < 0.01, life events p = 0.03. Conclusion Although previous studies have shown that stress axis function acts to moderate the risk of onset of some of these disorders, the present study shows that the degree of dysfunction is not correlated with a corresponding increasing load of disorders. The uncertainty surrounding the role of these biomarkers in the aetiology of unexplained disorders needs further investigation.